Investment and adaptation as commitment devices in climate politics - Clemens Heuson; Wolfgang Peters; Reimund Schwarze; Anna-Katharina Topp (Helmholtz-Zentrum für Umweltforschung (UFZ), 2013)
It is well established that adaptation and technological investment in each case may serve as a commitment device in international climate politics. This paper for the first time analyzes the combined impact of these two strategic variables on global mitigation within a noncooperative framework where countries either decide on mitigation before or after adaptation. By investment, which is assumed to be made in the first place due to its considerable lead time, countries commit to lower national contributions to the global public good of mitigation. We find that the sequencing of adaptation before mitigation reinforces this strategic effect of technological investments at least for sufficiently similar countries. As a consequence, the subgame-perfect equilibrium yields a globally lower level of mitigation and higher global costs of climate change when adaptation is decided before mitigation. Besides this theoretical contribution, the paper proposes some strategies to combat the unfortunate rush to adaptation which can be currently observed in climate politics.
Keywords: Q54; H41; H87; C72; 330; adaptation; climate policy; investment; mitigation; non-cooperative behavior